The association of FKBP5 polymorphisms with the severity of depressive disorder in patients with methamphetamine use disorders - Fang, Ting; Liu, Meng-Nan; Tian, Xiao-Yu; Lu, Guan-Yi; Li, Fei; Zhang, Xiaojie; Liu, Feng; Hao, Wei; Wu, Ning; Li, Hong; Li, Jin (Frontiers in Psychiatry, 2023)
Background Co-occurring depressive disorder (DD) in patients of methamphetamine use disorder (MAUD) impacts the diagnosis, treatment, and prognosis of the disease. Although FKBP5 has been associated with a variety of psychiatric disorders, whether FKBP5 influences depression susceptibility in MAUD is unknown so far. Methods Here, we sequenced six FKBP5 single-nucleotide polymorphism (SNP) sites (rs4713916, rs6926133, rs9470080, rs737054, rs4713902, and rs9470079) in 282 methamphetamine users. MAUD and DD were evaluated by clinical questionnaires. SPSS was used to analyze the relationship between FKBP5 SNPs and DD in individuals with MAUD. Results Of the 282 methamphetamine users, 161 individuals met the MAUD criteria, and among them, 50 patients (31.1%) had DD co-occurring. Importantly, the incidence of DD in individuals with MAUD was 3.314 times greater than that of the methamphetamine users who did not meet the MAUD criteria (p < 0.001). Although none of the six SNPs of FKBP5 were correlated with the co-occurrence of DD in the population with MAUD, two FKBP5 alleles (rs4713916A and rs6926133A) were substantially associated with the higher DD scores in patients with MAUD (p < 0.05). Moreover, those with the two risk alleles do not have much higher scores than those with a single risk allele, and the strong linkage disequilibrium of the two SNPs may be the underlying cause of this result. Despite having weak linkage disequilibrium with either rs4713916 or rs6926133, FKBP5 rs9470079 became risky when paired with either. Conclusion The results of this study revealed that the FKBP5 risk alleles (rs4713916A and rs6926133A) were associated with a greater probability of severe DD in patients with MAUD. These findings here would help with the development of biological early warning markers and the creation of personalized treatment strategies for MAUD.